2021
DOI: 10.1038/s41398-020-01164-y
|View full text |Cite
|
Sign up to set email alerts
|

The IL-6 antagonist tocilizumab is associated with worse depression and related symptoms in the medically ill

Abstract: Because medical illness is associated with increased inflammation and an increased risk for treatment-resistant major depressive disorder, anti-cytokine therapy may represent a novel, and especially efficacious, treatment for depression. We hypothesized that blockade of the interleukin (IL)-6 signaling pathway with tocilizumab would decrease depression and related symptomatology in a longitudinal cohort of allogeneic hematopoietic stem cell transplantation (HCT) patients, a medically ill population with a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 59 publications
1
27
1
Order By: Relevance
“…In MDD, we found some evidence to support that up-regulation of the IL-6R may be risk increasing conditioned on CRP and BMI, supporting preliminary data that blockade of IL-6R by agents such as tocilizumab may decrease depressive symptoms ( 45 ). However, data related to the antidepressant qualities of tocilizumab are conflicting ( 46 ), and randomized control trials are warranted to further investigate repurposing opportunities for IL-6 inhibition in MDD. Two recent studies also considered the effect of IL-6R signaling on the odds of depression via MR using some different GWAS than ours in some instances, with one study supporting a risk-increasing relationship between elevated IL-6R and depression ( 47 ), while the other suggested that IL-6R could be more specifically linked to suicidality rather than broad depression ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In MDD, we found some evidence to support that up-regulation of the IL-6R may be risk increasing conditioned on CRP and BMI, supporting preliminary data that blockade of IL-6R by agents such as tocilizumab may decrease depressive symptoms ( 45 ). However, data related to the antidepressant qualities of tocilizumab are conflicting ( 46 ), and randomized control trials are warranted to further investigate repurposing opportunities for IL-6 inhibition in MDD. Two recent studies also considered the effect of IL-6R signaling on the odds of depression via MR using some different GWAS than ours in some instances, with one study supporting a risk-increasing relationship between elevated IL-6R and depression ( 47 ), while the other suggested that IL-6R could be more specifically linked to suicidality rather than broad depression ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In MDD, we found some evidence to support that upregulation of the IL-6 receptor may be risk increasing conditioned on CRP and BMI, supporting preliminary data that blockade of IL-6R by agents like tocilizumab may improve depressive symptoms (82). However, data related to the anti-depressant qualities of tocilizumab are conflicting (83), and randomised control trials are warranted to further investigate repurposing opportunities for IL- 6 inhibition in MDD. Finally, BMI demonstrated a quite robust protective effect on OCD conditioned on CRP and IL-6 signalling, in accordance with observational data that OCD is associated with reduced odds of obesity (84).…”
Section: Discussionmentioning
confidence: 99%
“…In psychiatry, interleukin (IL)-6 has been identified as a potential target in patients with depression and schizophrenia using population cohort and genetic studies 24,25 . However, patients receiving IL-6 receptor blockade (tocilizumab) as acute graftversus-host-disease prophylaxis experienced significantly more depressive symptoms 26 . This indicates that further investigation is required to test the therapeutic potential of targeting the immune system specifically in patients with depression, such as the Insight study, a proof-of-concept experimental medicine trial of tocilizumab 27 .…”
Section: Tools/technology Developmentmentioning
confidence: 99%